PRESTASI AKADEMIK MAHASISWA YANG BEKERJA PARUH WAKTU DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Abdillah Syeach Putra; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
There are various reasons for students to study while working. The main reason is related to finance, namely earning income to pay for education and daily needs while reducing the burden on the family. Another reason is to fill spare time due to the lecture schedule that is not busy, want to live independently so as not to depend on other people or parents, seek experiences outside of college, pursue hobbies and various other reasons. The formulation..of.the problem discussed in this study is how the effect of part-time work activities on the academic achievement of FISIP Riau University students and how is the relationship between..gender..and academic achievement of students who study while working at FISIP, Riau University. The purpose of this study was to determine the effect of part-time work activities on academic achievement of FISIP Riau University students and the relationship between gender and academic achievement of students who work at FISIP, Riau University. The theory used is adaptation, goal, integration and latent of maintenance. Data analysis using correlation test. The data collection technique used in this study was a census technique with a total of 49 respondents. From the results of research in the field, it can be concluded that there is a very strong and significant influence between working part-time on the academic achievement of students at the Faculty of Social and Political Sciences, University of Riau and there is a low and significant relationship between gender on the academic achievement of students of the Faculty of Social Sciences. and Political Science, University of Riau. Keywords: Effect of Part-time Work, Academic Achievement, College Student.